2013
DOI: 10.1371/journal.pone.0076091
|View full text |Cite|
|
Sign up to set email alerts
|

Baseline Levels and Temporal Stability of 27 Multiplexed Serum Cytokine Concentrations in Healthy Subjects

Abstract: BackgroundCytokines are humoral molecules that elicit regulatory function in immunologic pathways. The level and type of cytokine production has become critical in distinguishing physiologic from pathologic immune conditions. Cytokine profiling has become an important biomarker discovery tool in monitoring of the immune system. However, the variations in cytokine levels in individual subjects over time in healthy individuals have not been extensively studied. In this study, we use multiplex bead arrays to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 20 publications
11
65
3
1
Order By: Relevance
“…For CCL5, the respective levels were from 10 264.21 pg/ml to 11 740.25 pg/ml. 40 These levels are coherent with our results.…”
Section: -38supporting
confidence: 92%
“…For CCL5, the respective levels were from 10 264.21 pg/ml to 11 740.25 pg/ml. 40 These levels are coherent with our results.…”
Section: -38supporting
confidence: 92%
“…For some assays, the proteins could not be detected in more than 60% of the tested sera (Table 2). Indeed, both platforms failed to robustly detect the GM-CSF, IL-1β, IL-2 and IL-5 cytokines for which previous investigations had reported significant variations in expression either during MDE treatment or at baseline in comparison to healthy controls (Biancotto et al, 2013;Dahl et al, 2014;Hernandez et al, 2008;Schmidt et al, 2014;Shelton et al, 2015). These types of inconsistency in the results have already been reported (Breen et al, 2011;Chaturvedi et al, 2011;Dabitao et al, 2011;Dupuy et al, 2013;Fu et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…In biological human fluids, the seasonal, hormonal, and circadian physiological variability in the circulating concentrations of cytokines/chemokines/growth factors remains poorly investigated both in psychiatric patients as a function of their treatments as well as in healthy subjects. Furthermore, large differences exist among individuals (Agorastos et al, 2014;Biancotto et al, 2013;Mueller et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, G-CSF, IL-12 and IL-17A levels were lower in patients with HCC compared to those in healthy adults. For other cytokines, previous studies showed the inconsistent results [31,32]. Therefore future study with healthy control, chronic hepatitis or liver cirrhosis will give more information about cytokine roles in patients with HCC.…”
Section: Discussionmentioning
confidence: 96%